Dynamic parameters for fluid responsiveness in mechanically ventilated children: A systematic review - Yenjabog, Patcha; Kanchongkittiphon, Wacharoot; Chutipongtanate, Somchai; Lertbunrian, Rojjanee; Ungprasert, Patompong (Frontiers in Pediatrics, 2022)
Objective: Fluid administration is the initial step of treatment of unstable pediatric patients. Evaluation of fluid responsiveness is crucial in mechanically ventilated children to avoid fluid overload, which increases mortality. We aim to review and compare the diagnostic performance of dynamically hemodynamic parameters for predicting fluid responsiveness in mechanically ventilated children. Design: A systematic review was performed using four electronic databases, including PubMed, EMBASE, Scopus, and Central, for published articles from 1 January 2010 to 31 December 2020. Studies were included if they described diagnostic performance of dynamic parameters after fluid challenge was performed in mechanically ventilated children. Settings: Pediatric intensive and cardiac intensive care unit, and operative room. Patients: Children aged 1 month to 18 years old who were under mechanical ventilation and required an intravenous fluid challenge. Measurements and Main Results: Twenty-seven studies were included in the systematic review, which included 1005 participants and 1138 fluid challenges. Respiratory variation in aortic peak velocity was reliable among dynamic parameters for predicting fluid responsiveness in mechanically ventilated children. All studies of respiratory variation in aortic peak velocity showed that the area under the receiver operating characteristic curve ranged from 0.71 to 1.00, and the cutoff value for determining fluid responsiveness ranged from 7% to 20%. Dynamic parameters based on arterial blood pressure (pulse pressure variation and stroke volume variation) were also used in children undergoing congenital heart surgery. The plethysmography variability index was used in children undergoing neurological and general surgery, including the pediatric intensive care patients. Conclusions: The respiratory variation in aortic peak velocity exhibited a promising diagnostic performance across all populations in predicting fluid responsiveness in mechanically ventilated children. High sensitivity is advantageous in non-cardiac surgical patients and the pediatric intensive care unit because early fluid resuscitation improves survival in these patients. Furthermore, high specificity is beneficial in congenital heart surgery because fluid overload is particularly detrimental in this group of patients.